Phytochemical Content, Antibacterial and Antioxidant Potential of Endemic Plant Anabasis aretioïdes Coss. & Moq. (Chenopodiaceae) - Senhaji, Souad (Biomed Res Int, 2020)
This study aims to investigate the biological activities of endemic plant Anabasis aretioïdes harvested in eastern Morocco. Various extracts were prepared from aerial part by aqueous and organic extraction using a Soxhlet and cold maceration. Preliminary phytochemical analysis was carried out on the powder and on the different extracts by standard phytochemical tests, and was confirmed by a quantitative analysis based on the determination of total polyphenols and cathechic tannins. Antioxidant activity was evaluated in vitro by five methods: H(2)O(2), DPPH, ABTS, FRAP, and RP, and the antibacterial activity was carried out by disc diffusion method and the determination of MIC and MBC. Phytochemical screening revealed the presence of cathechic tannins, saponins, and sterols and quantitative analysis showed that Ethyl acetate extract presented the high level of phenolic and cathechic tannins contents (46.79 ± 0.75 µg GAE/mg E and 46.46 ± 0.67 µg CE/mg E). A highest hydrogen peroxide activity was observed in aqueous macerated extract (7.84 ± 0.44%) and the macerated methanol extract has the highest rates for the other four antioxidant activity tests: It was able to reduce DPPH with an IC(50) of 52.91 ± 0.24 µg/ml, the highest ABTS•+ radical scavenging capacity (48.99 ± 1.316 µg TE/mg E), it showed also the highest antioxidant activity by the FRAP and reducing power test (99.73 ± 3.570 µg TE/mg E and 72.176 ± 0.540 µg AAE/mg E). Antibacterial screening showed that the maximum zone of inhibition was noted for ethyl acetate extract against Staphylococcus aureus (13.5 mm). The lowest MIC value was obtained with methanolic and macerated methanolic extracts against Protéus mirabilis strain (MIC = 3.125 mg/ml). Principal component analysis showed that the four methods ABTS, DPPH, FRAP, and RP are highly correlated and a correlation between the antioxidant activity and the total phenolic contents of the extracts indicated that phenolic compounds were the dominant contributors to the antioxidant activity of the plant.